Improving Sitting Endurance with the Use of Economic Tokens in Children with Attention Deficit and Hyperactivity Disorders (Single Subject Research class V at SDN 06 Piai Tangah) - Rurri Handalusia; Zulmiyetri Zulmiyetri; Gaby Arnez (Universitas Muhammadiyah Enrekang, 2023)
This research focuses on the problems experienced by ADHD students who are unable to stay seated while studying . The aim of this research is to increase endurance while sitting in learning and also to provide enthusiasm in participating in learning by using economic tokens. This research uses an experimental method using SSR (Single Subject Research). This research data was collected through observation and documentation. The results of this research can be said that the use of economic tokens is effective in increasing sitting endurance in children with ADHD.